Solution of Boundary Value Problems Using Dual Reciprocity Boundary Element Method (Advances in Applied Mathematics and Mechanics, 2018)
In this work we utilize the boundary integral equation and the Dual ReciprocityBoundary Element Method (DRBEM) for the solution of the steady stateconvection-diffusion-reaction equations with variable convective coefficients in two-dimension.The DRBEM is a numerical method to transform the domain integrals intothe boundary only integrals by using the fundamental solution of Helmholtz equation.Some examples are calculated to confirm the accuracy of the approach. The resultsobtained by the analytic solutions are in good agreement with ones provided by theDRBEM technique.